2002
DOI: 10.1021/bi025819z
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Domains, Transmembrane Segments, and Intracellular Domains Interact To Determine the Cation Selectivity of Na,K- and Gastric H,K-ATPase

Abstract: We have previously reported that three residues of the fourth transmembrane segment (TM4) of the Na,K- and gastric H,K-ATPase alpha-subunits appear to play a major role in the distinct cation selectivities of these pumps [Mense, M., et al. (2000) J. Biol. Chem. 275, 1749-1756]. Substituting these three residues in the Na,K-ATPase sequence with their H,K-ATPase counterparts (L319F, N326Y, T340S) and replacing the TM3-TM4 ectodomain sequence with that of the H,K-ATPase alpha-subunit result in a pump that exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Similar to our results, Mense et al (37) found this substitution to be responsible for conferring the Na,K-ATPase with a Na-independent ATPase activity and a dependency toward protons. In that work, however, Thr345 alone was important but not sufficient to induce the enzymatic changes mentioned and substitutions in the Na,K-ATPase of two additional residues (Leu319 and Thr340), as well as the TM3-TM4 ectodomain of the H,K-ATPase were also required (38). Our results show that substitutions confined to transmembrane domain 4 are able to alter Na + selectivity of the enzyme.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Similar to our results, Mense et al (37) found this substitution to be responsible for conferring the Na,K-ATPase with a Na-independent ATPase activity and a dependency toward protons. In that work, however, Thr345 alone was important but not sufficient to induce the enzymatic changes mentioned and substitutions in the Na,K-ATPase of two additional residues (Leu319 and Thr340), as well as the TM3-TM4 ectodomain of the H,K-ATPase were also required (38). Our results show that substitutions confined to transmembrane domain 4 are able to alter Na + selectivity of the enzyme.…”
Section: Discussionmentioning
confidence: 50%
“…The function of the TMAll mutant indicates that transmembrane domains are not sufficient to confer Na + selectivity to the Na,K-ATPase and other domains are involved. Our observation confirms previous results by Mense at al., who show that cytoplasmic, as well as extracellular, domains interact to create the particular properties of P-type ATPases (38).…”
Section: Discussionmentioning
confidence: 99%
“…3. This part includes only animal IIC ATPases that, generally, may be considered bona fide a-HKAs and a-NKAs (Mense et al 2002;Jorgensen et al 2003). There is no bootstrap support for the separation of both sub-trees (i.e., below 50%).…”
Section: Resultsmentioning
confidence: 99%
“…1). Identification of the subunit domains involved in assembly and trafficking of Na,KATPase has been approached by immune precipitation experiments with truncated ␤-subunits (12,13) and chimeras between the Na,K-ATPase and gastric H,K-ATPase ␣-subunits (14,15).…”
mentioning
confidence: 99%